A specific mutation abolishing Na+/H+ antiport activity in hamster fibroblasts precludes growth at neutral and acidic pH. - Pouysségur, J (1984)
A H+-suicide technique based on the reversibility of Na+/H+ antiport was developed for the selection of mutants deficient in this membrane-bound activity. The strategy was to use the Na+/H+ antiporter as a H+-vector killing device. Chinese hamster lung fibroblasts (CCL39) were loaded with LiCl and incubated in Na+-, Li+-free choline Cl saline solution (pH 5.5). Under these conditions, intracellular pH dropped in 5 min from 7.1 to 4.8, leading to a rapid loss of cell viability (less than 0.1% survival after 30 min). Cytoplasmic acidification and cell death were prevented by treatment with 5-N,N-dimethylamiloride, a potent inhibitor of Na+/H+ antiport. Of the H+-suicide resistant clones that survived two cycles of selection, 90% were found deficient in Na+/H+ antiport activity. One class of mutants (PS10, PS12) fully resistant to the H+-suicide test, does not acidify the cell interior in response to an outward-directed Li+ gradient and has no detectable amiloride-sensitive Na+ influx measured either in Li+- or H+-loaded cells. Growth of these fibroblast clones lacking Na+/H+ antiport was found to be pH conditional in HCO3(-)-free medium. Whereas wild-type cells can grow over a wide range of external pHs (6.6-8.2), PS mutants cannot grow at neutral and acidic pHs (pH less than 7.2); their optimal growth occurs at alkaline pH values (pH 8-8.3). These findings strongly suggest that the Na+/H+ antiport activity through regulation of intracellular pH plays a crucial role in growth control.